Estimation of Relationship between Inflation and Relative Price Variability: Granger Causality and ARDL Modelling Approach - Saghir Pervaiz Ghauri; Rizwan Raheem Ahmed; Jolita Vveinhardt; Dalia Streimikiene (Amfiteatru Economic Journal, 2017)
The objective of this research paper is to examine the relationship between relative price variability and inflation by using consumer price index (CPI) of Pakistan. The outcomes of the research further divided into food and non-food groups too. The monthly data of CPI was taken from the Pakistan Bureau of Statistics, from August 2001 to July 2011 (with 2000-01 base) for 92 composite commodities with 12 sub-groups. We employed the Granger causality testing approach for the evaluation of any possible influence of one indicator to another. In this scenario, it is viable to state that there is a presence of causality and bidirectional feedback between the variables or the two variables are independent. The major issue is to identify a suitable statistical method that enables us to analyze the association among the variables. The findings of this study demonstrated that there is a probable relationship between inflation (DPt) and both un-weighted measures of price variability (VPt and SPt) for the whole items that have been considered for the analysis. Apart from that, this association also exists between food and non-food categories of CPI basket.
Keywords: B23; E30; E31; E52; 330; CPI basket; consumer price index; food & non-food group; inflation; Granger-causality; relative price variability